2017
DOI: 10.1111/jfr3.12312
|View full text |Cite
|
Sign up to set email alerts
|

Flooding hazard assessment at Tulancingo (Hidalgo, Mexico)

Abstract: In recent decades, the Tulancingo municipality (Mexico), has been affected by numerous extreme weather phenomena that caused heavy flooding events with severe damage to property and people. Most of the weather phenomena placed several dams under hydrologic risk. The hurricane ‘Dean’, in 2007, led to the overflow of the dam ‘La Esperanza’, generating inundations that reached levels of 1 m in Tulancingo. Mexico does not have a specific regulation that establishes critical thresholds for the construction of flood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
8
0
2
Order By: Relevance
“…They compared observed and modeled flood frequencies for the period 1970-2010, and found that, recently, the most frequent floods are the result of a rapid and intense deforestation process. Bonasia et al [52] realized a flooding hazard assessment at Tulancingo in the state of Hidalgo. The authors developed a methodology for evaluating downstream flooding probability and associated inundation maps to support long-term mapping and minimize flood impact.…”
Section: Flood Maps and Existing Applicationsmentioning
confidence: 99%
“…They compared observed and modeled flood frequencies for the period 1970-2010, and found that, recently, the most frequent floods are the result of a rapid and intense deforestation process. Bonasia et al [52] realized a flooding hazard assessment at Tulancingo in the state of Hidalgo. The authors developed a methodology for evaluating downstream flooding probability and associated inundation maps to support long-term mapping and minimize flood impact.…”
Section: Flood Maps and Existing Applicationsmentioning
confidence: 99%
“…29 Nº 4 -2018el cual ha tenido un uso considerable en el contexto iberoamericano para modelar inundaciones fluviales (Bonasia et al, 2017;Bodoque et al, 2016). El software de IBER cuenta con una interfaz en pre y post proceso muy sencilla e intuitiva.…”
Section: Pérezunclassified
“…IBER 2D consta de diferentes módulos: turbulencia, transporte de sedimentos e hidrodinámica, constituyendo este último, la base de la herramienta empleando las ecuaciones de St. Venant 2D de aguas someras resueltas bajo el método de volúmenes finitos y sometidas al principio de conservación de la materia y de momento en las dos direcciones horizontales (Bladé et al, 2014). IBER 2D ha sido empleado en múltiples estudios de hidráulica aplicada: inundaciones fluviales (Bonasia et al, 2017), evaluación de medidas de restauración para pequeños cauces (Castillo et al, 2014), ruptura de represas (Álvarez et al, 2017) y transporte de material leñoso en ríos (Ruiz et al, 2015). Un input importante en IBER es la topografia a través de un MDT.…”
Section: Conceptualización De La Modelación: La Herramienta Iber 2dunclassified
“…The model has been widely applied to analyse flooding problems. The reader can obtain a detailed explanation of this type of problems in [9] and [10].…”
Section: Numerical Modelmentioning
confidence: 99%